Silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization (C sp3 –C sp2 ) via memory of chirality: access to circumdatin alkaloids - Mahajan, Pankaj S.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization has been developed to form a Csp3–Csp2 bond via memory of chirality. The application of the process has been demonstrated for the synthesis of the circumdatin class of alkaloids in high enantiopurity with retention of the configuration. The developed protocol is mild and works with an inexpensive silver catalyst in the absence of ligand, base, or additives. The involvement of a monoradical in the reaction has been established by trapping the radical intermediate.